2004
DOI: 10.1029/2004jd004876
|View full text |Cite
|
Sign up to set email alerts
|

Weather systems occurring over Fort Simpson, Northwest Territories, Canada, during three seasons of 1998–1999: 1. Cloud features

Abstract: [1] An investigation of high-latitude continental cloud systems was carried out in the interior of the Northwest Territories of Canada during three multiweek periods during the fall, winter, and spring of 1998-1999 as part of the Canadian Global Energy and Water Cycle Experiment (GEWEX) Enhanced Study. Radar data supplemented by satellite, upper air, and surface observations were used to determine the seasonal behavior of cloud macroscopic properties and compare these with similar observations elsewhere. Uniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Zhang et al (1996) found that the surface net radiation balance under cloudy conditions depended strongly on cloud microphysical properties, cloud base temperature, and cloud thickness, and variability in these properties could produce variations in the onset of snow melt of more than a month. Radar studies have shown that numerical weather prediction models frequently overpredict high cloud and underpredict low cloud (Hudak et al, 2004;Hogan et al, 2001;Hinkelman et al, 1999). Hudak et al (2004) also found a significant diurnal cycle in cloud properties during winter, especially cloud thickness and cloud occurrence, both of which increased at night; consistent with radiatively induced circulations driven by cloud top infra-red cooling (Lazarus et al, 2000).…”
Section: B Cold Snow -Vapour Deposition Feedback?mentioning
confidence: 64%
See 1 more Smart Citation
“…Zhang et al (1996) found that the surface net radiation balance under cloudy conditions depended strongly on cloud microphysical properties, cloud base temperature, and cloud thickness, and variability in these properties could produce variations in the onset of snow melt of more than a month. Radar studies have shown that numerical weather prediction models frequently overpredict high cloud and underpredict low cloud (Hudak et al, 2004;Hogan et al, 2001;Hinkelman et al, 1999). Hudak et al (2004) also found a significant diurnal cycle in cloud properties during winter, especially cloud thickness and cloud occurrence, both of which increased at night; consistent with radiatively induced circulations driven by cloud top infra-red cooling (Lazarus et al, 2000).…”
Section: B Cold Snow -Vapour Deposition Feedback?mentioning
confidence: 64%
“…Radar studies have shown that numerical weather prediction models frequently overpredict high cloud and underpredict low cloud (Hudak et al, 2004;Hogan et al, 2001;Hinkelman et al, 1999). Hudak et al (2004) also found a significant diurnal cycle in cloud properties during winter, especially cloud thickness and cloud occurrence, both of which increased at night; consistent with radiatively induced circulations driven by cloud top infra-red cooling (Lazarus et al, 2000).…”
Section: B Cold Snow -Vapour Deposition Feedback?mentioning
confidence: 64%
“…The net radiation deficit at the surface contributes to the development of deep and enduring surface-based temperature inversion layers that characterize much of the basin during the winter. Being under the influence of the broad climatological high pressure ridge and mean subsidence, winter clouds in the basin are typically shallow and have low cloud bases that are close to the top of the inversion layer (Stewart and Burford 2002;Hudak et al 2004). As such, cloud-base temperatures are often higher than surface temperatures and clouds typically exert a positive surface radiative forcing over the basin.…”
Section: Anticyclogenesis and Development Of Cold Air Massmentioning
confidence: 99%
“…A number of major field programs have been conducted in the Canadian Arctic. Data sets collected during the Beaufort and Arctic Storms Experiment [ Hanesiak et al ., ; Stewart et al ., ; Hudak et al ., ] and the Mackenzie Global Energy and Water Cycle Experiment Study [ Stewart et al ., ; Asuma et al ., ] and the Storm Studies in the Arctic (STAR) [ Gascon et al ., ; Henson et al ., ; Laplante et al ., ; Fargey et al ., ], among others, have been analyzed with the purpose of characterizing Arctic clouds, precipitation, and storm systems. Unique features included the prevalence of multilayered systems, the cold temperatures of low clouds, and the significant sublimation effects in the initial stages of storm events and between cloud layers [ Stewart et al ., ; Henson et al ., ; Laplante et al ., ].…”
Section: Introductionmentioning
confidence: 99%